CONSERVATION OF THE MURAL PAINTINGS OF THE GREEK ORTHODOX CHURCH DOM E OF SAINT GEORGE, OLD CAIRO-EGYPT - Abd El-Tawab, N.; Mahran, A.; Gad, K. (European Scientific Journal, ESJ, 2014)
The church of Mary Girgis (Saint George) was built by Athanasius "who also founded the Church of Saints Cyrus and John". The Church was destroyed, and all the rest of the original edifice is a room which covered by huge dome known as the Wedding Hall, dating to the 14th century. The huge dome of the wedding Hall contains several mural paintings represented Coptic arts. The dome mural paintings was darkened and severely damaged as significant detachments of the painted layer and the underneath support lost their cohesion and separated into many pieces, delamination and flaking of the ceiling painting. The most important causes for the monument state of degradation were the environmental condition such as the effects of the groundwater, the presence of salts, the humidity (active in all its forms as infiltration, capillarity and condensation) and the improper previous interventions at the structural level (fillings in the cracks with gypsum mortars). The aim of this study is to characterize the components of the pictorial surface which consists of pigments, the binding media, the plaster layer and its support and introduce the conservation project of the mural painting which was carried out at the dome "between" 2004-20013. Prior to the conservation intervention, the materials were characterized by optical microscopy, polarizing microscope, scanning electron microscopy with energy dispersive X-ray spectroscopy, X-ray diffraction and X-ray fluorescence. The chemical analyses have determined the nature and composition of the materials used in the painting process (mortars, pigments, binders), have identified the causes of physical and chemical altering processes of pigment layers and provided knowledge on the execution technique. The interior painting was executed according to the Byzantine technique, on a fresco plaster (intonaco) consisting of lime mortar, pigments were obtained by mixing pigments with water. After the material characterization, the conservation and restoration of the mural painting, which including cleaning, injection grouting, fixation of the paint layer, filling of the support gaps with mortar, consolidation, restoration and completion of lost parts, were carried out.